Quality of extension advice: a gendered case study from Ghana and Sri Lanka. Issue 1 (1st January 2017) - Lamontagne-Godwin, Julien; Williams, Frances; Bandara, Willoru Mudiyansele Palitha Thilakasiri; Appiah-Kubi, Ziporah
ABSTRACT: Purpose : Women farmers have less access to extension services than male farmers, even though they make up almost half of the global agricultural workforce. Gender-focused international development programmes have focused on how ensuring women receive better access to advice. However, the quality of the technical advice and the service women receive in comparison to male farmers needs better understanding. Study design/methodology/approach : Five thousand interactions between male and female extension workers ('plant doctors') and farmers attending Plantwise plant clinics in Ghana and Sri Lanka are assessed for gender-based differences on quality of advice and service provided at clinics. Findings : The overall quality of technical advice given to male and female farmers at plant clinics in both countries did not differ. The quality of the advice given by male and female plant doctors for a specific pest/crop complex was different, and can be linked to results from the quality of service surveys that revealed women's main negative feedback was the impracticality of advice. Practical implications : Whilst the advice given is technically sound, results highlight the importance of appropriate advice, according to farmer gender and crop grown. Theoretical implications : A greater focus on plant doctors using their knowledge about women's role in agriculture would help to achieve more tailored advice. Originality/Value : This study leads the way in assessing the quality of the advice given according to gender. With large datasets, this research should help decision makers and future researchers to contemplate advice delivery according to gender.